ANALISIS ABNORMAL RETURN SEBELUM DAN SESUDAH MELAKUKAN CORPORATE ACTION STOCK SPLIT MAUPUN RIGHTS ISSUE (Studi pada Perusahaan yang Terdaftar di Bursa Efek Indonesia) - M Minhaj Awabi (Jurnal Ilmu Manajemen, 2023)
This study aims to determine whether there are differences in abnormal returns before and after the rights issue or stock split. Sampling was conducted using a purposive sampling technique and obtained as many as 33 companies for rights issue events and 55 companies for stock split events. The observation period was conducted 5 days before and 5 days after the event. The analysis technique used was the Wilcoxon Signed Ranks Test using IBM Statistics SPSS 26 with a significance level of 5%. The results showed that there were no differences in abnormal returns before and after the rights issue, and there were differences in abnormal returns before and after the stock split. This shows that a stock split has information content and the market does react. This study provides practical implications that the company must have a strategy to attract the attention of investors when carrying out a rights issue, and the companies can do a stock split if they want to increase liquidity.